2010
DOI: 10.1038/ejcn.2009.146
|View full text |Cite
|
Sign up to set email alerts
|

Associations between child weight and maternal feeding styles are mediated by maternal perceptions and concerns

Abstract: ObjectiveTo determine whether controlling parental feeding practices are associated with children’s adiposity and test the hypothesis that any associations are mediated by maternal perception of their child’s weight.MethodChildren aged 7-9 yrs (n=405) were weighed and measured at school as part of the Physical Exercise and Appetite in CHildren Study (PEACHES). Adiposity was indexed with BMI SD-scores. The Child Feeding Questionnaire (CFQ) was completed by 53% of mothers of participating children (n=213). Mothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

31
195
7
9

Year Published

2012
2012
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 196 publications
(242 citation statements)
references
References 37 publications
(48 reference statements)
31
195
7
9
Order By: Relevance
“…This suggests that parents who exert higher levels of Covert Control might replace the home availability of unhealthy snacks by home availability of fruit, which is positively related to fruit intake (15,20,22,52) . Consistent with previous findings (23) , Encouragement was negatively related to child energy-dense snack intake, indicating that parental encouragement might be influenced by health beliefs: parents encourage their children's interest in and curiosity for a variety of healthy foods, resulting in the consumption of less unhealthy foods (23,49) .…”
Section: Discussionsupporting
confidence: 86%
“…This suggests that parents who exert higher levels of Covert Control might replace the home availability of unhealthy snacks by home availability of fruit, which is positively related to fruit intake (15,20,22,52) . Consistent with previous findings (23) , Encouragement was negatively related to child energy-dense snack intake, indicating that parental encouragement might be influenced by health beliefs: parents encourage their children's interest in and curiosity for a variety of healthy foods, resulting in the consumption of less unhealthy foods (23,49) .…”
Section: Discussionsupporting
confidence: 86%
“…Specifically, the children receiving increased pressure to eat had a lower BMI, BMI z score, %BF, and waist circumference compared with their cotwins. Previous studies have shown this association between pressure to eat and lower child weight status across families, 39,40 and experimental studies have found that pressuring children to eat (eg, "Finish your soup, please") can have counterproductive effects on a child' s eating and food preferences. 41 Pressuring a child to eat beyond satiety might also contribute to excess weight gain.…”
Section: Discussionmentioning
confidence: 99%
“…Mothers generally use more restriction when they perceive their child as overweight or when they are concerned about the child becoming overweight in the future. 35,[45][46][47][48] Pressuring is more common in mothers who perceive their child as underweight. 35,45,47 However, most of these studies have focused on higher income white families who are unlikely to be food insecure.…”
Section: Discussionmentioning
confidence: 99%